Moderating role of training transfer in determining entrepreneurial performance among micro, small and medium enterprises owners in Lagos State, Nigeria - Kabiru Ishola, Genty (2016)
Despite the significance and contributions of micro, small and medium enterprises (MSMEs) to the national economy, many problems and constraints still exist in promoting their development and growth which invariably affect the performance of the owners. This, in turn, led to the dwindling number of MSMEs in Nigeria. The declines were attributed to poor personal traits of entrepreneurs in Nigeria, underdeveloped human resources, and the harsh operating business environment. In addition, MSMEs failure, particularly in emerging economies, has been attributed to lack of preparedness as a result of inaccurate entrepreneurial training and lack of training transfer of entrepreneur skills and competencies. However, very few studies have been conducted in Nigeria to ascertain entrepreneurial performance and factors influencing entrepreneurial performance collectively. Thus, this study general objective determines the moderating role of training transfer on the determinants of entrepreneurial performance. At the same time examines holistically the determinant factors influencing entrepreneurial performance in Lagos State Nigeria taking into consideration the multi-determinant constructs of personal qualities of the entrepreneurs, business competencies, and environmental munificence factors. This is because entrepreneurial performance has been argued in literature to be multidimensional phenomena; hence studying entrepreneurial performance in isolation makes such findings inconclusive. Therefore, investigating multi-determinant relationships becomes imperative. The study adopted a quantitative approach using a survey while Cochran (1977) formulae for sample size determination was used to calculate for the sample size. Descriptive statistic tool was used for demographic data analysis as well as to determine the level of the used constructs in the study. The Structural Equation Modelling (SEM) approach was utilised to test the stated research hypotheses. Prior to full utilisation of the model, the researcher ensure the model meet the acceptable goodness-of-fit indices: X2 (CMIN) = 387.238 (DF = 196), Relative X2 (CMIN/DF) = 1.976, AGFI = .870, GFI = .899, CFI = .939, IFI = .939, TLI = .928 and RMSEA = .056. The study descriptive analysis revealed that there is a moderate level of entrepreneurial performance among the 307 valid respondents with a mean score of 4.08 (SD= 1.43). More so, the analysis depicted that the level of entrepreneurs personal qualities was high at a mean score of 3.81 (SD =1.13). Similarly, business competencies level among the respondents was also high with a mean score of 4.25 (SD = 0.86). However, the respondents level of environmental munificence factors were moderate with a mean score of 3 (SD = 1.33), while, the training transfer level was high at a mean score of 4.27 (SD = 0.81). The structural equation model showed that personal qualities did not significantly contribute to entrepreneurial performance (β = -.109, p = .108). However, the analysis of structural equation model depicted that business competencies contributed significantly to entrepreneurial performance (β = -.127, p = .043), though the contribution was negatively related. In addition, training transfer contributions to entrepreneurial performance was estimated at (β = .323, p = .000) which was also significant with high positive effect size when compared to the relationship with business competencies and entrepreneurial performance. The structural model revealed that the relationship between personal qualities, business competencies, and environmental munificence factors are moderated by training transfer in the study with measurement residual X2 greater than unconstrained X2 based on model comparison output ΔX2 (CMIN) = 10.925; Δdf = 40; p = .000. Therefore, the study showed that there is a presence of moderation effect of training transfer on the determinants of entrepreneurial performance in the overall model. Based on the findings from the study, the researcher concluded that the moderate level of entrepreneurial performance among the manufacturing MSMEs owners in Lagos State, Nigeria was attributed to the contributions of training transfer on the relationship between business competencies and entrepreneurial performance. This implies that high level of training transfer enhances business competencies of the respondents which in turn improve their entrepreneurial performance. Therefore, there is need for Nigeria MSMEs owners to place more emphasis on human resource development, and training transfer in particular in order to increase entrepreneurial performance in Nigeria. Thus, this study suggests for more effective entrepreneurial training that will allows for transfer of training necessary for the enhancement of personal qualities, business competencies and environmental munificence factors among the MSMEs owners. The study findings can serve as a guide in developing entrepreneurial training curriculum, selection of resource persons, and pedagogical methods require to inculcating the personal qualities, business competencies, and environmental munificence factors necessary for entrepreneurial performance among the trainees.